Stain-resistant glazed travertine porcelain tile and preparation method thereof
By modifying and modifying the surface of the cave stone decorative layer of the cave stone porcelain tiles, using catecholamine to fill the micro holes, and forming transparent enamel in secondary firing, the pollution resistance of the cave stone porcelain tiles in the prior art is solved. The problem of insufficient results has achieved higher density and anti-fouling performance.
Patent Information
- Application Number
- CN202411624966.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the existing preparation process of clay porcelain tiles, the organic particles in the blank powder volatility is uncertain, resulting in microscopic holes left on the surface of clay, reducing the pollution resistance of clay bricks.
The base layer, fog decorative layer and glaze layer structures are stacked from bottom to top, and the surface of the fog decorative layer is modified and modified. The fog decorative layer is oxidative and self-polymerized in the wet state is used to fill the fog ceramic bricks. Miniature holes on the surface of the embryo and transparent enamel is formed in secondary firing.
The compactness and stain resistance of the surface of the cave stone porcelain tiles have been significantly improved, making the porcelain tiles more dirt-resistant and easy to clean and maintain in actual use.
Smart Images

Figure CN119430893A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic tiles, and in particular to a stain-resistant glazed travertine porcelain tile and a preparation method thereof. Background Art
[0002] Travertine, scientifically known as travertine, is a porous rock, so people usually call it travertine. Travertine belongs to terrestrial sedimentary rock, which is a calcium carbonate deposit. Travertine is mostly formed in limestone terrain rich in calcium carbonate. It is formed by calcium carbonate and other minerals dissolved in water deposited on riverbeds, lake bottoms, etc. Because pores sometimes appear during the heavy accumulation process, and because its main component is calcium carbonate, it is easily dissolved and corroded by water, so there will be many natural irregular holes in these deposits. Natural travertine has a natural and simple decorative effect, clear texture, gentle and rich texture, and has always been a high-end building decoration material, but due to limited materials, high cost and high price, it is limited to a large number of uses; with the continuous advancement of ceramic process equipment and decoration methods, people have always hoped to develop artificial stones with shapes and decorative effects close to natural stones and low costs to replace natural travertine, and ceramic tiles are the best products to imitate natural travertine. Through the improvement of ceramic tile preparation methods, it is constantly approaching natural travertine, and travertine texture bricks came into being.
[0003] Since the existing travertine preparation process mostly uses volatilization to restore the irregular holes of natural travertine, this method uses organic particles to the green body powder, which is pressed into shape and then dried at high temperature. During the drying process, the organic particles are volatilized by heat, leaving a corresponding hole structure in the green body. However, due to the uncertainty of the volatilization of organic particles in the green body powder, microscopic holes will be left on the surface of the travertine. These microscopic holes on the surface will cause dirt to be easily adsorbed on the surface of the travertine ceramic tile, resulting in a decrease in the anti-fouling ability of the travertine ceramic tile. Summary of the invention
[0004] In order to solve the above technical problems, a stain-resistant glazed travertine porcelain tile and a preparation method thereof are provided. The technical solution solves the above-mentioned problem that the uncertainty of volatilization of organic particles present in the green body powder will leave microscopic holes on the surface of the travertine. These microscopic holes on the surface will cause dirt to be easily adsorbed on the surface of the travertine porcelain tile, resulting in a decrease in the stain resistance of the travertine porcelain tile.
[0005] In order to achieve the above purpose, the technical solution adopted by the present invention is:
[0006] A stain-resistant glazed travertine porcelain tile comprises: a base layer, a travertine decorative layer and a glaze layer stacked in sequence from bottom to top;
[0007] The upper surface of the travertine decorative layer is subjected to a modification process using a modification solution;
[0008] The thickness of the travertine decoration layer is 25%-30% of the base layer.
[0009] Preferably, the modified solution is prepared by mixing catecholamine and tris(hydroxymethyl)aminomethane solution in a weight-to-volume ratio of 1 kg:200 L.
[0010] Preferably, the base layer is composed of the following components in terms of mass percentage:
[0011] Clay 25%-40%, quartz sand 50%-60%, reinforcing material 15%-20%;
[0012] The reinforcing material is composed of one or more components of kaolin, feldspar, limestone, slag and pigment.
[0013] Preferably, the travertine decorative layer is composed of 10%-15% of foaming material and 85%-90% of base layer components according to mass percentage;
[0014] The foaming material consists of 15%-50% ball clay, 20%-35% low-temperature frit powder, 5%-15% graphite powder and 25%-35% calcium carbonate powder in terms of mass percentage.
[0015] Preferably, the glaze layer is composed of the following components in terms of mass percentage:
[0016] Quartz sand 65%-85%, calcium carbonate 5%-15%, vanadium 5%-10%, lead-free glaze 5%-15%.
[0017] Furthermore, a preparation process of a stain-resistant glazed travertine porcelain tile is proposed, which is applicable to the stain-resistant glazed travertine porcelain tile as described above, and comprises the following steps:
[0018] According to the composition ratio of the base layer and the travertine decorative layer, the corresponding weights of the components are weighed, mixed, ground and spray-dried into powders to obtain base layer powders and travertine decorative layer powders;
[0019] According to the thickness ratio of the base layer and the travertine decorative layer, double-layer fabrication is performed, and dry pressing is performed to obtain the travertine porcelain tile embryo;
[0020] The travertine porcelain tile embryo is dried at 200° C. for 5-10 minutes to obtain a travertine porcelain tile dry embryo;
[0021] The dried travertine porcelain tile embryo is sent into a kiln for firing once to obtain a travertine porcelain tile embryo;
[0022] The travertine decorative layer of the travertine porcelain tile blank is immersed in sulfuric acid with a volume fraction of 10%, and then washed and dried at 55° C.-65° C. for 2 hours to obtain a travertine porcelain tile pickled blank;
[0023] The travertine porcelain tile acid-washed embryo travertine decorative layer is immersed in a modification solution, and the modification is carried out at 70°C-75°C for 2-3 hours, and then the modification is carried out after washing and drying to obtain a travertine porcelain tile surface modified embryo;
[0024] According to the mass percentage of the glaze layer, the corresponding mass components are weighed and mixed, and then ground and spray-dried into powder to obtain glaze powder, and the glaze powder is mixed with water in a mass percentage ratio of 1:1, ball milled for 12 minutes, and passed through a 250-mesh sieve to obtain a glaze;
[0025] The surface of the travertine porcelain tile is modified with a rough travertine decorative layer according to 10g / m 3 The water is sprayed with a certain amount of water, and then glazed through the glazing line;
[0026] The surface modified embryo of the glazed travertine porcelain tile is sent into a kiln for secondary firing to obtain a glazed travertine porcelain tile.
[0027] Optionally, the process parameters of the primary firing are:
[0028] Firing at 850℃-1050℃ for 1h-1.5h.
[0029] Optionally, the process parameters of the secondary firing are:
[0030] Firing at 1100℃-1250℃ for 1h-1.5h.
[0031] Optionally, the preparation process of the tris(hydroxymethyl)aminomethane solution specifically includes:
[0032] 2.422 kg of tris(hydroxymethyl)aminomethane was dissolved in 190 L of water, and a hydrochloric acid solution with a concentration of 0.1 mol / L was added to make the volume to 200 L to obtain a tris(hydroxymethyl)aminomethane solution.
[0033] Optionally, the acid-washed travertine decorative layer of the travertine ceramic tile is immersed in a modification solution, modified at 70° C.-75° C. for 2-3 hours, and then cleaned and dried. During the modification process, the modification solution is in a shaking state.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] The present invention proposes a novel glazed travertine porcelain tile, which is prepared by a secondary firing glazing method. The surface of the travertine porcelain tile blank produced by the primary firing is modified, and catecholamine is used to undergo an oxidative self-polymerization reaction in a wet state. The self-polymerization product can firmly adhere to the surface of a solid matrix, fill the micro-pores on the surface of the travertine porcelain tile blank, and increase the density of the travertine porcelain tile surface. After that, the glazing is performed for a secondary firing to form a layer of transparent glaze on the surface of the travertine porcelain tile blank, so that the glazed surface remains smooth and dense at the micro-pores while retaining the macro-decorative pores, thereby effectively improving the anti-fouling ability of the travertine porcelain tile surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a process flow chart of the preparation of the stain-resistant glazed travertine porcelain tile proposed by the present invention;
[0037] Figure 2 It is a schematic diagram of the chemical reaction of the modification process in the present invention;
[0038] Figure 3 This is a microscopic image of the surface of the travertine porcelain tile blank of the present invention;
[0039] Figure 4 This is a microscopic image of the surface of the travertine porcelain tile surface modified embryo in the present invention. DETAILED DESCRIPTION
[0040] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0041] Embodiment 1:
[0042] A stain-resistant glazed travertine porcelain tile comprises: a base layer, a travertine decorative layer and a glaze layer stacked in sequence from bottom to top;
[0043] The base layer is composed of the following components by mass percentage:
[0044] Clay 25%, quartz sand 60%, reinforcing material 15%, the reinforcing material is composed of one or more components of kaolin, feldspar, limestone, slag, pigment. Kaolin can improve the refractoriness and whiteness of tiles, making them more beautiful and durable. Feldspar can improve the hardness and wear resistance of tiles. Limestone can improve the compressive performance of tiles. Slag can improve the refractoriness and chemical corrosion resistance of tiles. Pigments are used to adjust the color and texture of tiles to meet different decorative requirements. In actual production, one or more of them can be selected as reinforcing materials according to production requirements.
[0045] The travertine decorative layer is composed of 15% of foaming material and 85% of base layer components by mass percentage, and the foaming material is composed of 50% of ball clay, 20% of low-temperature frit powder, 5% of graphite powder, and 25% of calcium carbonate powder by mass percentage;
[0046] The glaze layer is composed of the following components in terms of mass percentage:
[0047] Quartz sand 85%, calcium carbonate 5%, vanadium 5%, lead-free glaze 5%.
[0048] The upper surface of the travertine decorative layer is treated with a modification solution through a modification process;
[0049] The thickness of the travertine decorative layer is 25% of the base layer.
[0050] Embodiment 2:
[0051] A stain-resistant glazed travertine porcelain tile comprises: a base layer, a travertine decorative layer and a glaze layer stacked in sequence from bottom to top;
[0052] The base layer is composed of the following components by mass percentage:
[0053] Clay 40%, quartz sand 50%, reinforcing material 10%, the reinforcing material is composed of one or more components of kaolin, feldspar, limestone, slag, pigment. Kaolin can improve the refractoriness and whiteness of tiles, making them more beautiful and durable. Feldspar can improve the hardness and wear resistance of tiles. Limestone can improve the compressive performance of tiles. Slag can improve the refractoriness and chemical corrosion resistance of tiles. Pigments are used to adjust the color and texture of tiles to meet different decorative requirements. In actual production, one or more of them can be selected as reinforcing materials according to production requirements.
[0054] The travertine decorative layer is composed of 10% of foaming material and 90% of base layer components according to mass percentage, and the foaming material is composed of 15% of ball clay, 35% of low-temperature frit powder, 15% of graphite powder, and 35% of calcium carbonate powder according to mass percentage;
[0055] The glaze layer is composed of the following components in terms of mass percentage:
[0056] Quartz sand 65%, calcium carbonate 15%, vanadium stone 10%, lead-free glaze 10%.
[0057] The upper surface of the travertine decorative layer is treated with a modification solution through a modification process;
[0058] The thickness of the travertine decorative layer is 30% of the base layer.
[0059] Embodiment three:
[0060] A stain-resistant glazed travertine porcelain tile comprises: a base layer, a travertine decorative layer and a glaze layer stacked in sequence from bottom to top;
[0061] The base layer is composed of the following components by mass percentage:
[0062] Clay 35%, quartz sand 55%, reinforcing material 10%, the reinforcing material is composed of one or more components of kaolin, feldspar, limestone, slag, pigment. Kaolin can improve the refractoriness and whiteness of tiles, making tiles more beautiful and durable. Feldspar can improve the hardness and wear resistance of tiles. Limestone can improve the compressive performance of tiles. Slag can improve the refractoriness and chemical corrosion resistance of tiles. Pigments are used to adjust the color and texture of tiles to meet different decorative needs. In actual production, one or more of them can be selected as reinforcing materials according to production needs.
[0063] The travertine decorative layer is composed of 15% of foaming material and 85% of base layer components by mass percentage, and the foaming material is composed of 30% of ball clay, 30% of low-temperature frit powder, 10% of graphite powder, and 30% of calcium carbonate powder by mass percentage;
[0064] The glaze layer is composed of the following components in terms of mass percentage:
[0065] Quartz sand 75%, calcium carbonate 10%, vanadium 5%, lead-free glaze 10%.
[0066] The upper surface of the travertine decorative layer is treated with a modification solution through a modification process;
[0067] The thickness of the travertine decorative layer is 25% of the base layer.
[0068] Example 4, a preparation process of a stain-resistant glazed travertine porcelain tile, referring to Figure 1 As shown, the following steps are included:
[0069] According to the composition ratio of the base layer and the travertine decorative layer provided in Example 1, the corresponding weights of the components are weighed, mixed, ground and spray-dried into powders to obtain base layer powders and travertine decorative layer powders;
[0070] According to the thickness ratio of the base layer and the travertine decorative layer provided in Example 1, double-layer fabrication is performed, and dry pressing is performed to obtain a travertine ceramic tile embryo;
[0071] The travertine porcelain tile embryo is dried at 200° C. for 5-10 minutes to obtain a travertine porcelain tile dry embryo;
[0072] The dried travertine porcelain tile body is sent into a kiln and fired at 850°C-1050°C for 1h-1.5h to obtain a travertine porcelain tile blank body;
[0073] The travertine decorative layer of the travertine porcelain tile blank is immersed in sulfuric acid with a volume fraction of 10%, and then washed and dried at 55°C-65°C for 2 hours to obtain a travertine porcelain tile pickled blank. The pickling process further roughens the microscopic pores on the surface of the travertine porcelain tile blank, providing a better adhesion environment for the subsequent polycatecholamine;
[0074] The acid-washed travertine decorative layer of the travertine porcelain tile is immersed in a modification solution, and the modification is carried out at 70°C-75°C for 2-3 hours, and then the modification is washed and dried. During the modification, the modification solution is in a shaking state, and the surface modification of the travertine porcelain tile is obtained;
[0075] According to the mass percentage composition ratio of the glaze layer provided in Example 1, the corresponding mass components are weighed, mixed, ground and spray-dried into powder to obtain glaze powder, the glaze powder is mixed with water in a mass percentage ratio of 1:1, ball milled for 12 minutes, and passed through a 250-mesh sieve to obtain a glaze;
[0076] The surface of the travertine porcelain tile is modified with a rough travertine decorative layer according to 10g / m 3 The water is sprayed with a certain amount of water, and then glazed through the glazing line;
[0077] The glazed travertine porcelain tile surface modified embryo is sent into a kiln and fired at 1100° C.-1250° C. for 1 h-1.5 h to obtain a glazed travertine porcelain tile, which is recorded as porcelain tile A.
[0078] Example 5, a preparation process of a stain-resistant glazed travertine porcelain tile, referring to Figure 1 As shown, the following steps are included:
[0079] According to the composition ratio of the base layer and the travertine decoration layer provided in Example 2, the corresponding weights of the components are weighed, mixed, ground and spray-dried into powders to obtain base layer powders and travertine decoration layer powders;
[0080] According to the thickness ratio of the base layer and the travertine decorative layer provided in Example 2, double-layer fabrication is performed, and dry pressing is performed to obtain a travertine ceramic tile embryo;
[0081] The travertine porcelain tile embryo is dried at 200° C. for 5-10 minutes to obtain a travertine porcelain tile dry embryo;
[0082] The dried travertine porcelain tile body is sent into a kiln and fired at 850°C-1050°C for 1h-1.5h to obtain a travertine porcelain tile blank body;
[0083] The travertine decorative layer of the travertine porcelain tile blank is immersed in sulfuric acid with a volume fraction of 10%, and then washed and dried at 55°C-65°C for 2 hours to obtain a travertine porcelain tile pickled blank. The pickling process further roughens the microscopic pores on the surface of the travertine porcelain tile blank, providing a better adhesion environment for the subsequent polycatecholamine;
[0084] The acid-washed travertine decorative layer of the travertine porcelain tile is immersed in a modification solution, and the modification is carried out at 70°C-75°C for 2-3 hours, and then the modification is washed and dried. During the modification, the modification solution is in a shaking state, and the surface modification of the travertine porcelain tile is obtained;
[0085] According to the mass percentage composition ratio of the glaze layer provided in Example 2, the corresponding mass components are weighed and mixed, and then ground and spray-dried into powder to obtain glaze powder, and the glaze powder is mixed with water in a mass percentage ratio of 1:1, ball milled for 12 minutes, and passed through a 250-mesh sieve to obtain a glaze;
[0086] The surface of the travertine porcelain tile is modified with a rough travertine decorative layer according to 10g / m 3 The water is sprayed with a certain amount of water, and then glazed through the glazing line;
[0087] The glazed travertine porcelain tile surface modified embryo is sent into a kiln and fired at 1100° C.-1250° C. for 1 h-1.5 h to obtain a glazed travertine porcelain tile, which is recorded as porcelain tile B.
[0088] Example 6, a preparation process of a stain-resistant glazed travertine porcelain tile, referring to Figure 1 As shown, the following steps are included:
[0089] According to the composition ratio of the base layer and the travertine decoration layer provided in Example 3, the corresponding weights of the components are weighed, mixed, ground and spray-dried into powders to obtain base layer powders and travertine decoration layer powders;
[0090] According to the thickness ratio of the base layer and the travertine decorative layer provided in Example 3, double-layer fabrication is performed, and dry pressing is performed to obtain a travertine ceramic tile embryo;
[0091] The travertine porcelain tile embryo is dried at 200° C. for 5-10 minutes to obtain a travertine porcelain tile dry embryo;
[0092] The dried travertine porcelain tile body is sent into a kiln and fired at 850°C-1050°C for 1h-1.5h to obtain a travertine porcelain tile blank body;
[0093] The travertine decorative layer of the travertine porcelain tile blank is immersed in sulfuric acid with a volume fraction of 10%, and then washed and dried at 55°C-65°C for 2 hours to obtain a travertine porcelain tile pickled blank. The pickling process further roughens the microscopic pores on the surface of the travertine porcelain tile blank, providing a better adhesion environment for the subsequent polycatecholamine;
[0094] The acid-washed travertine decorative layer of the travertine porcelain tile is immersed in a modification solution, and the modification is carried out at 70°C-75°C for 2-3 hours, and then the modification is washed and dried. During the modification, the modification solution is in a shaking state, and the surface modification of the travertine porcelain tile is obtained;
[0095] According to the mass percentage composition ratio of the glaze layer provided in Example 3, the corresponding mass components are weighed and mixed, and then ground and spray-dried into powder to obtain glaze powder, and the glaze powder is mixed with water in a mass percentage ratio of 1:1, ball milled for 12 minutes, and passed through a 250-mesh sieve to obtain a glaze;
[0096] The surface of the travertine porcelain tile is modified with a rough travertine decorative layer according to 10g / m 3 The water is sprayed with a certain amount of water, and then glazed through the glazing line;
[0097] The glazed travertine porcelain tile surface modified embryo is sent into a kiln and fired at 1100° C.-1250° C. for 1 h-1.5 h to obtain a glazed travertine porcelain tile, which is recorded as porcelain tile C.
[0098] The sizes of porcelain tile A, porcelain tile B and porcelain tile C are all 1200mm×600mm, and the thickness is 20mm.
[0099] The modified solution is prepared by mixing catecholamine and tris(hydroxymethyl)aminomethane solution in a weight-to-volume ratio of 1kg:200L.
[0100] The configuration process of the tris(hydroxymethyl)aminomethane solution specifically includes:
[0101] 2.422 kg of tris(hydroxymethyl)aminomethane was dissolved in 190 L of water, and a hydrochloric acid solution with a concentration of 0.1 mol / L was added to make the volume to 200 L to obtain a tris(hydroxymethyl)aminomethane solution.
[0102] During the modification process, the chemical reactions of catecholamines are as follows: Figure 2 As shown: Catecholamine undergoes self-polymerization reaction under acidic conditions to generate polycatecholamine. The micro-pores on the surface of the travertine porcelain tile embryo provide a good attachment environment for polycatecholamine. Therefore, polycatecholamine will firmly adhere to the surface of the solid matrix and fill the micro-pores on the surface of the travertine porcelain tile embryo.
[0103] This scheme adopts the method of secondary firing and glazing for preparation. The surface of the travertine porcelain tile blank produced by the first firing is modified and the catecholamine is used to undergo an oxidative self-polymerization reaction in a wet state. The self-polymerization product can firmly adhere to the surface of the solid matrix, fill the micro-pores on the surface of the travertine porcelain tile blank, and increase the density of the travertine porcelain tile surface. After that, the glazing is applied and the second firing is performed to form a layer of transparent glaze on the surface of the travertine porcelain tile blank, so that the glaze surface remains smooth and dense at the micro-pores while retaining the macro-decorative pores.
[0104] Several samples of porcelain tile A, porcelain tile B, and porcelain tile C were prepared according to the preparation processes of the stain-resistant glazed travertine porcelain tiles disclosed in Example 4, Example 5, and Example 6, respectively;
[0105] Several samples of porcelain tile A, porcelain tile B and porcelain tile C were tested according to the test method for ceramic tiles specified in GB-T 4100-2015, and the obtained data are shown in the following table:
[0106]
[0107] It can be seen from the above table that the glazed travertine porcelain tile prepared by this scheme has excellent compressive resistance, and because the micro-pores on the surface of the travertine base are firmly attached and filled with polycatecholamine, the density of the travertine surface is improved, thereby effectively reducing the water absorption rate of the travertine porcelain tile, and effectively improving the anti-fouling ability of the travertine porcelain tile.
[0108] Microstructure Analysis:
[0109] The surface of the travertine porcelain tile blank during the preparation process of porcelain tile C was micro-enlarged, and the microscopic image obtained was as follows: Figure 3 As shown;
[0110] The surface modification embryo of the travertine porcelain tile during the preparation process of porcelain tile C was micro-enlarged, and the microscopic image obtained was as follows: Figure 4 As shown;
[0111] from Figure 3 and Figure 4 It can be clearly seen that the microscopic pores on the surface of the modified travertine are obviously filled, while the macroscopic pores on the surface of the travertine are retained. The structural density of the travertine surface is greatly increased, which effectively ensures the surface anti-fouling ability of the travertine porcelain tile.
[0112] In summary, the advantages of the present invention are: the surface of the travertine porcelain tile blank formed in a single firing process is modified and treated, and the density of the surface of the travertine porcelain tile is significantly improved by utilizing the oxidative self-polymerization reaction of catecholamines in a wet state. This treatment method allows the glaze surface of the finally fired porcelain tile to achieve a smooth and dense effect at the microscopic holes while retaining the macroscopic decorative holes. In this way, the anti-fouling ability of the travertine porcelain tile surface is effectively improved, making it more resistant to dirt and easier to clean and maintain during actual use.
[0113] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. A stain-resistant glazed travertine porcelain tile, characterized in that: include: The base layer, travertine decoration layer and glaze layer are stacked from bottom to top; The upper surface of the travertine decorative layer is subjected to a modification process using a modification solution; The thickness of the travertine decoration layer is 25%-30% of the base layer.
2. The preparation process of a stain-resistant glazed travertine porcelain tile according to claim 1, characterized in that: The modified solution is prepared by mixing catecholamine and tris(hydroxymethyl)aminomethane solution in a weight-to-volume ratio of 1kg:200L.
3. The stain-resistant glazed travertine porcelain tile according to claim 2, characterized in that: The base layer is composed of the following components in terms of mass percentage: Clay 25%-40%, quartz sand 50%-60%, reinforcing material 10%-20%; The reinforcing material is composed of one or more components of kaolin, feldspar, limestone, slag and pigment.
4. The stain-resistant glazed travertine porcelain tile according to claim 3, characterized in that: The travertine decorative layer is composed of 10%-15% of foaming material and 85%-90% of base layer components according to mass percentage; The foaming material consists of 15%-50% ball clay, 20%-35% low-temperature frit powder, 5%-15% graphite powder and 25%-35% calcium carbonate powder in terms of mass percentage.
5. The stain-resistant glazed travertine porcelain tile according to claim 4, characterized in that: The glaze layer is composed of the following components in terms of mass percentage: Quartz sand 65%-85%, calcium carbonate 5%-15%, vanadium stone 5%-10%, lead-free glaze 5%-10%.
6. A process for preparing a stain-resistant glazed travertine porcelain tile, applicable to the stain-resistant glazed travertine porcelain tile as claimed in any one of claims 1 to 5, characterized in that: The steps include: According to the composition ratio of the base layer and the travertine decorative layer, the corresponding weights of the components are weighed, mixed, ground and spray-dried into powders to obtain base layer powders and travertine decorative layer powders; According to the thickness ratio of the base layer and the travertine decorative layer, double-layer fabrication is performed, and dry pressing is performed to obtain the travertine porcelain tile embryo; The travertine porcelain tile embryo is dried at 200° C. for 5-10 minutes to obtain a travertine porcelain tile dry embryo; The dried travertine porcelain tile embryo is sent into a kiln for firing once to obtain a travertine porcelain tile embryo; The travertine decorative layer of the travertine porcelain tile blank is immersed in sulfuric acid with a volume fraction of 10%, and then washed and dried at 55° C.-65° C. for 2 hours to obtain a travertine porcelain tile pickled blank; The travertine porcelain tile acid-washed embryo travertine decorative layer is immersed in a modification solution, and the modification is carried out at 70°C-75°C for 2-3 hours, and then the modification is carried out after washing and drying to obtain a travertine porcelain tile surface modified embryo; According to the mass percentage of the glaze layer, the corresponding mass components are weighed and mixed, and then ground and spray-dried into powder to obtain glaze powder, and the glaze powder is mixed with water in a mass percentage ratio of 1:1, ball milled for 12 minutes, and passed through a 250-mesh sieve to obtain a glaze; The surface of the travertine porcelain tile is modified with a rough travertine decorative layer according to 10g / m 3 The water is sprayed with a certain amount of water, and then glazed through the glazing line; The surface modified embryo of the glazed travertine porcelain tile is sent into a kiln for secondary firing to obtain a glazed travertine porcelain tile.
7. The process for preparing a stain-resistant glazed travertine porcelain tile according to claim 6, characterized in that: The process parameters of the primary firing are: Firing at 850℃-1050℃ for 1h-1.5h.
8. The process for preparing a stain-resistant glazed travertine porcelain tile according to claim 7, characterized in that: The process parameters of the secondary firing are: Firing at 1100℃-1250℃ for 1h-1.5h.
9. The process for preparing a stain-resistant glazed travertine porcelain tile according to claim 8, characterized in that: The configuration process of the tris(hydroxymethyl)aminomethane solution specifically includes: 2.422 kg of tris(hydroxymethyl)aminomethane was dissolved in 190 L of water, and a hydrochloric acid solution with a concentration of 0.1 mol / L was added to make the volume to 200 L to obtain a tris(hydroxymethyl)aminomethane solution.
10. The process for preparing a stain-resistant glazed travertine porcelain tile according to claim 9, characterized in that: The acid-washed travertine decorative layer of the travertine porcelain tile is immersed in a modification solution, modified at 70° C.-75° C. for 2-3 hours, and then cleaned and dried. During the modification process, the modification solution is in a shaking state.
Citation Information
Patent Citations
Method for preparing three-dimensional cavitation travertine ceramic tile
CN104045375A
Functional modification method for surface and interface of material based on polyphenol compounds
CN105218847A
Ceramic tile with travertine structure and preparation method thereof
CN114804845A
Steel fiber surface modification treatment method
CN117245086A